Assessment of the Oxidative Desulfurization of Middle Distillate Surrogate Fuels with Spectroscopic Techniques - Eleni Syntyhaki; Anastasia Detsi; Dimitrios Karonis (Journal of Analytical Methods in Chemistry)
The oxidative desulfurization of five (5) model sulfur compounds and eleven (11) surrogate blends was investigated using the hydrogen peroxide (H2O2)-acetic acid (CH3COOH) system. Consequently, extractive desulfurization was carried out using conventional solvents. The model sulfur compounds, as well as the solvent, are present in petroleum middle distillates. The selection of the compounds was made so that they represent various kinds of sulfur compounds. The goal of this study was the implementation of a simple and economical oxidative and extractive system for the desulfurization of surrogate mixtures with an intermediate sulfur concentration 1% w/w, at the mild temperature of 70°C, and without the use of supplementary and assisting methods such as heterogeneous catalysis or ultrasound irradiation. The sulfur content was estimated using X-ray fluorescence. The progress of the oxidation reaction was monitored using liquid FT-IR. The solid sediments of the oxidation procedure were identified with solid-state FT-IR and 1H NMR spectroscopy.